ACTUAL PROBLEMS OF EDUCATIONAL INTEGRATION OF STUDENTS IN THE SLOVAK REPUBLIC - Hladush, V.; Klein, V.; Šilonová, Viera (Актуальні питання корекційної освіти (педагогічні науки), 2019)
The article deals with the actual problems of integration processes in the Slovak Republic educational sphere in the last 10 years and highlights the main tendencies, discussion questions and practical tasks concerning the attraction of pupils with special educational needs to general mass educational institutions. The focus is on the latest statistics from the European Agency for Special Needs and Inclusive Education that Slovakia belongs to the group of EU Member States with the highest percentage of students with special educational needs (more than 4%) who are educated in segregated educational institutions. The article analyzed the total number of students, in particular primary school pupils, special grades of primary schools, special primary schools, but above all pupils with special educational needs integrated into elementary schools. The article presents the number of gifted children. The article highlights some aspects and activities of diagnostic institutions (public and private) and the quality of the study level of children development, which directly affects the efficiency of the functioning of integrated educational institutions and special schools. The proposals on solving urgent problems of integration processes in the educational sphere are formulated in this scientific research